Infecções odontogênicas graves: etiologia microbiana, perfil de citocinas e de suscetibilidade a drogas antimicrobianas - Augusto Cesar Sette Dias (2016)
Odontogenic infections are defined as polymicrobial processes that affect the teeth or their supporting structures, being associated with the interaction between indigenous microbiota and host. Due to possible complications in the course of the disease, emergent hospitalization might be necessary. Considering the paucity of data on the topic, the aim of this study was to evaluate the susceptibility profile of isolated bacteria, the expression of cytokines/chemokines and the microbiota associated with severe odontogenic infection. In order to evaluate antimicrobial susceptibility profile, we followed CLSI guidelines. To determine the profile of cytokine expression, samples of pus obtained from 12 patients and 12 control individuals were included in the investigation. Real time PCR was employed to quantify the expression of TNF-á IL-1â, IL-17A, IFN-ã, IL-10, TGF-â, IL-8, CCL2 and CCL5. Regarding to microbial profile, the microbiota of 38 patients with the disease was evaluated by metagenomics HOMINGS (Human Oral Microbe Identification Using Next Generation Sequencing). A total of 74 isolates were obtained from 30 hospitalized patients presenting odontogenic infections. When the whole study group was evaluated, higher resistance rates were observed for erythromycin and clindamycin (about 45% and 30%, respectively). Among anaerobes, the highest resistance rates were about 45% for metronidazol and 25% for clindamycin. Regarding to cytokines expression, high amounts of the proinflammatory cytokines: IFN-ã, TNF-á, IL-17A, IL-1â and the chemokines: IL-8, CCL2/MCP-1, were observed. While, low expression of the chemokine CCL5 and anti-inflammatory cytokines: IL-10 and TGF- â was observed. Regarding to microbial profile, it was observed an average of 88 species per patient, with the prevalence of Rothia dentocariosa and Parvimona micra. These results contribute to our knowledge about the interrelationship between pathogenic microorganisms and the response orchestrated by the host in a condition of severe oral infection.